2020
DOI: 10.1016/j.ebiom.2020.103081
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning-based clustering robustly identified two classes of sepsis with both prognostic and predictive values

Abstract: Background Sepsis is a heterogenous syndrome and individualized management strategy is the key to successful treatment. Genome wide expression profiling has been utilized for identifying subclasses of sepsis, but the clinical utility of these subclasses was limited because of the classification instability, and the lack of a robust class prediction model with extensive external validation. The study aimed to develop a parsimonious class model for the prediction of class membership and validate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 46 publications
2
62
0
Order By: Relevance
“…A multi-layer perceptron was then trained on these supertiles to predict gene expression data. During training, only the top k [ 1 , 2 , 5 , 10 , 20 , 50 ] , 100 tiles in terms of predicted gene expression are selected and a weighted mean computed of their predictions, giving more weight to higher valued predictions. Finally, the model is fine-tuned for specific organs using the 8000 normal tiles, again sampling the top k [ 10 , 20 , 50 ], 100, 200, 500, 1000, 2000, 5000 during training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi-layer perceptron was then trained on these supertiles to predict gene expression data. During training, only the top k [ 1 , 2 , 5 , 10 , 20 , 50 ] , 100 tiles in terms of predicted gene expression are selected and a weighted mean computed of their predictions, giving more weight to higher valued predictions. Finally, the model is fine-tuned for specific organs using the 8000 normal tiles, again sampling the top k [ 10 , 20 , 50 ], 100, 200, 500, 1000, 2000, 5000 during training.…”
Section: Discussionmentioning
confidence: 99%
“…Abdullal et al compared a multilayer perceptron to traditional regression to predict susceptibility to COVID-19 [49] . Zhang et al utilized genetic algorithms to develop an autoencoder to extract and cluster features related to gene expression to predict susceptibility to sepsis [50] . Shashikumar et al developed an interpretable recurrent neural network to pre-emptively predict sepsis based on temporal features such as heart rate and arterial pressure [51] .…”
Section: Introductionmentioning
confidence: 99%
“…However, one of the most important challenges in the management of critically ill patients is the population heterogeneity [16] , [17] , [18] , [19] . The idea of protective ventilation is theoretically sound but may be difficult to implement in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have explored associations between immune signatures and clinical prognosis based on blood transcriptomic profiling in patients [10] , [11] . For example, based on whole blood gene expression profiling, Zhang et al identified two subtypes of sepsis, which displayed different immune responses and clinical outcomes [10] . Shankar et al identified transcriptomic features in blood to predict paediatric patients with multiple organ dysfunction in need of intensive care [11] .…”
Section: Introductionmentioning
confidence: 99%